DEVELOPING STUDENTS’ SPEAKING SKILLS AS A PEDAGOGICAL PROBLEM - Prenova Gulsara Barlikbaevna (Bright Mind Publishing, 2025)
This article explores the development of students’ speaking skills as a central pedagogical problem in modern education. It highlights the importance of oral communication for academic success and social integration, emphasizing the role of effective teaching strategies in fostering these skills. The study examines factors that hinder and enhance speaking proficiency, including psychological, linguistic, and methodological aspects. Special attention is given to interactive and student-centered approaches, such as communicative language teaching, task-based learning, and the integration of authentic speaking activities into the curriculum. The article concludes by proposing practical recommendations for educators to support the systematic development of students' oral communication abilities.
Keywords: Speaking skills, language learning, oral communication, pedagogy, communicative competence, student-centered learning, task-based learning, education strategies.